PERUBAHAN FUNGSI KOGNITIF DENGAN CAIRAN REHIDRASI PADA SISWA SMA MUHAMMADIYAH 1 KOTA SEMARANG - Yuliana Noor Setiawati Ulvie; Siti Aimah (Universitas Muhammadiyah Semarang, 2017)
Lack of fluid consumption causes adolescent susceptible to dehydration. Dehydration is a condition of body fluid imbalance because fluid expenditure is greater than income. Dehydration occurs in adolescents (48.1%) than adults (44.5%). Dehydration results in impaired cognitive function, neurologic function and ultimately affects quality of life. Rehydration is needed to cope with the effects of dehydration. Rehydration is the process of recovering / replacing lost body fluids. The purpose of this research is to know the change of cognitive function with rehydration fluid in SMA Muhammadiyah 1 Semarang students. The type and designof the study were experimental comparison group pre-test and post test desaign. The population is students of SMA Muhammadiyah 1 Semarang. Sampling method using stratified random side. The sample used is 30 high school students. The subjects were divided into 3 groups, namely control group, mineral water, andisotonic drink. Prior to the treatment of the subjects the study carried out the measurement of body weight, total body water and cognitive function using code and memory test then induction of sport by running.Research subjects re-measurement of cognitive function after exercise. using code and memory tests. Intergroup memory changes were analyzed by Mann-Whitney test. The results showed a decreased average memory in the after-dehydration state than before dehydration. There was a significant improvement in memory function after rehydration in the rehydrated group with isotonic beverages (p = 0.006) and mineral water (p = 0.026). There was a significant decrease in memory function (p = 0.035) in the group without rehydration. In cognitive function between groups, there were significant differences (p = 0,022) between groups. Dehydration decreases a person's cognitive function otherwise rehydration with isotonic drinks and mineral water can improve a person's cognitive function. Keywords: Rehidration, dehydration, cognitive, isotonic water, mineral water